PREMIER WOLNYCH ŁUŻYC - Suwart, Adam (Wydawnictwo Naukowe UAM, 2009)
Wojciech Kóćka’s life could easily serve as a source material of many action and historical film screenplays. He has been hunted by the Nazi, has gone into hiding following threads by the NKVD and have had not an easy life in the first years of the communist Poland. In 1945 he was regarded as the most serious candidate for the position o f Prime Minister of a Lusatian Free State. He has never repudiated his Lusatian roots and became one of the most eminent intellectuals in the post-war era.
THE PRIME MINISTER OF A LUSATIAN FREE STATE